Role of Financial Inclusion in Poverty Alleviation in Jigawa State Nigeria; the Moderating Effect of Financial Literacy - YOLA TURAWA, ABDULNASIR; Jakada, Aminu; Nadira Madaki Iliyasu, Nadira Madaki Iliyasu; Abdullahi Dayyabu Marmara, Abdullahi Dayyabu Marmara (Journal of Economics and Administrative Sciences, 2025)
A need for research that examines how financial inclusion alleviates poverty in Jigawa state with a specific focus on the moderating effect of financial literacy. The study utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM). Financial inclusion was found to contribute to poverty alleviation by granting access to essential financial amenities like loans, savings, and insurance. Additionally, financial literacy significantly curbs this relationship by enhancing the efficiency of financial inclusion in poverty alleviation. Individuals who utilize financial services more effectively were found to have higher financial literacy, resulting in improved financial stability, increased savings, and investments in income-generating activities. Recommendation from the findings suggests the implementation of financial literacy programs, the promotion of inclusive financial services and the leveraging of digital financial technologies. Furthermore, the vulnerable group should be focused on by integrating financial education into school curricula as a strategy for maximizing poverty alleviation through the impact of financial inclusion.